A CRISPR–Cas9 system for multiple genome editing and pathway assembly in Candida tropicalis. Issue 2 (28th November 2019) - Zhang, Lihua; Zhang, Haibing; Liu, Yufei; Zhou, Jingyu; Shen, Wei; Liu, Liming; Li, Qi; Chen, Xianzhong
Abstract: Genetic manipulation is among the most important tools for synthetic biology; however, modifying multiple genes is extremely time‐consuming and can sometimes be impossible when dealing with gene families. Here, we present a clustered regularly interspaced short palindromic repeat (CRISPR) and CRISPR‐associated protein 9 (Cas9) system for use in the diploid yeast Candida tropicalis that is vastly superior to traditional techniques. This system enables the rapid and reliable introduction of multiple genetic deletions or mutations, as well as a stable expression using an integrated CRISPR–Cas9 cassette or a transient CRISPR–Cas9 cassette, together with a short donor DNA. We further show that the system can be used to promote the in vivo assembly of multiple DNA fragments and their stable integration into a target locus (or loci) in C. tropicalis . Based on this system, we present a platform for the biosynthesis of β‐carotene and its derivatives. These results enable the practical application of C. tropicalis and the application of the system to other organisms. Abstract : Genetic manipulation is among the most important tools for synthetic biology; however, modifying multiple genes is extremely time‐consuming and can sometimes be impossible when dealing with gene families